2011
DOI: 10.1111/j.1464-410x.2010.10000.x
|View full text |Cite
|
Sign up to set email alerts
|

The Z‐shaped ileal neobladder after radical cystectomy: an 18 years experience with 329 patients

Abstract: Eighty-three early complications in 80/294 patients (27.2%) occurred. The average Clavian rate of these early complications was 2.24. Among these, 12 complications in 12 patients (4.1%) were pouch-related, and 3 reoperations were required. Two patients died from cardiac complications. Sixty-three late complications in 60/294 patients (20.4%) were recorded. The average Clavian rate of these late complications was 2.98. Among these, 47 complications in 45/294 patients (15.3%) were pouch-related, and 18 reoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Martínez-Cornelio et al reported metabolic acidosis as the most frequent early complication of neobladder formation in their centre, demonstrated in 66% of patients 4 . In another case series, Neuzillet et al reported a 15% complication rate of metabolic acidosis and all of these cases responded well to oral medication 5 . In a large study involving 1,000 neobladders, Hautmann et al found that 70% of patients had metabolic acidosis in the early post-operative period, which was easily treated with sodium bicarbonate 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Martínez-Cornelio et al reported metabolic acidosis as the most frequent early complication of neobladder formation in their centre, demonstrated in 66% of patients 4 . In another case series, Neuzillet et al reported a 15% complication rate of metabolic acidosis and all of these cases responded well to oral medication 5 . In a large study involving 1,000 neobladders, Hautmann et al found that 70% of patients had metabolic acidosis in the early post-operative period, which was easily treated with sodium bicarbonate 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the authors used a standardised definition of UTI, referring to the consensus conference of the AFSSAPS (Agence Française de Sécurité Sanitaire des Produit de Santé) . In the study of Hautmann et al.…”
Section: Studies Describing Rfn As a Secondary Outcomementioning
confidence: 99%
“…Although most studies used SCr measurements, IVU , and CT for laboratory and morphological assessment of RFn, none provided absolute figures in the results section. Neuzillet et al.…”
Section: Studies Describing Rfn As a Secondary Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The large contemporary orthotopic neobladder cohorts (mainly including male patients) have shown daytime continence rates of 87-95.9% [55][56][57][58][59] after a median follow-up of 32-57 months. Due to a loss of the detrusor-sphincter reflex increasing the outlet pressure of the sphincter during filling of the bladder, night-time continence rates are lower (72-95%).…”
Section: Continencementioning
confidence: 99%